THE ROLE OF 'SCHOOL OF WORK' IN TECHNICAL EDUCATION - Henryk, NOGA; KIELBASA, Marzena (Trends in education, 2012)
Technical education seems to be of marginal significance when discussing the phenomenon of the educational evolution in Poland, which may cause certain anxiety. The presence of technical education in teaching programs is highly desirable as it can not only let pupils get familiar with modern technological achievements but can also help to systematize the basics of knowledge of technology and can influence conscious choice of a further education path. The initiative taken to bring technical education to schools should include its historical conditioning too.The work below is an attempt to present the main principles of 'school of work', its historical conditioning and theory.
Keywords: School of work; didactics of technology; history of technological education.